Quotas and Gender Competence: Independent or Complementary Approaches to Gender Equality? - Wroblewski, Angela (Frontiers in Sociology, 2021)
Austrian gender equality policy in higher education is characterized by the successful implementation of a comprehensive set of gender equality policies and persistent gender imbalances. After the introduction of a legal quota for university bodies, for instance, female representation in decision-making bodies increased significantly within a short period of time. However, this did not lead to a cultural change or the abolishment of barriers to women’s careers. Research has attributed this paradoxical situation to a lack of reflexivity because the current gender equality policies do not force institutions or individuals to challenge traditional practices, which are perceived to be merit-based and therefore gender neutral. To overcome this paradox, the Austrian Federal Ministry of Education, Science, and Research launched a policy process aimed at strengthening gender competence in all higher education processes—management, administration, teaching, and research. This paper provides a critical discussion of the Austrian quota regulation and its implementation. It also introduces the concept of gender competence and outlines the underlying assumptions as to why the new policy is expected to contribute to change. Following a critical reflection on these assumptions, the paper also discusses how existing steering instruments have to be adapted to support individual and institutional reflexivity.